Cropping systems mapping through high resolution imagery - Blasch, Gerald; Zepeda, Adair; Schulthess, Urs; Sonder, Kai; Lopez-Ridaura, Santiago (CIMMYT, 2025)
Real composition of crops landscape relays on secondary measurements and official statistics. Those information sources are based on surveys or technicians’ evaluations, with a probable gap between measurements and reality. In this study in Oaxaca's Mixteca region (Mexico) a high-definition satellite images were tested with a ground plot-inventory to calibrate a rando forest model for classification.